Musculoskeletal structure of the shoulder and arm in large flying fox (Pteropus vampyrus) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Cahyadi DD, Nurhidayat, Nisa’ C, Supratikno, Novelina S, Setijanto H, Agungpriyono S. 2022. Musculoskeletal structure of the shoulder and arm in large flying fox (Pteropus vampyrus). Biodiversitas 23: 5902-5913. The flight activity of bats is the most energy-consuming activity compared to other locomotion activities. The anatomical characteristic of its musculoskeletal system is believed to play important role in their flight ability. The present study aimed to describe the musculoskeletal morphology of the shoulder, arms, and wing of the large flying fox (Pteropus vampyrus). In this study, the parameters used are observing the specific body parts of the shoulder and arm skeletons and muscles, comparing skeletons and muscles of the other species of bats and related literature. The arm and wing skeleton of the large flying fox were relatively simple, lengthened, and  flexible at the distal end of the distal most phalanx, demonstrating the flexibility of a  flying fox’s arm and wing during flight. The muscles involved in flying movement that moved the wings, either in adduction or in abduction. The muscles that play a role in the wing adduction phase of the large flying fox are musculi (mm.) pectorales, musculus (m.) serratus ventralis thoracis, m. clavodeltoideus, and m. biceps brachii caput coracoideus. Conversely, the wing abduction phase is played by several main muscles, such as m. clavotrapezius, m. acromiotrapezius, m. latissimus dorsi, m. teres major, m. acromiodeltoideus, m. spinodeltoideus, m. triceps brachii caput laterale, and m. triceps brachii caput longum. Briefly, the musculoskeletal characteristics of the shoulder and arms of the large flying fox are suggested as morphological adaptation to allow free shoulder area movement, reduce the body mass, and resist the large torsional stress in the wing.
Keywords: Kalong, morphology, musculoskeletal, Pteropus vampyrus, shoulder, wing